2011
DOI: 10.1007/s10658-011-9882-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plant stage and organ age on the receptivity of Pisum sativum to Mycosphaerella pinodes

Abstract: International audienceOn spring pea, ascochyta blight (Mycosphaerellapinodes) frequently appears at the plant base on yellowing stipules and disease scores are higher on basal parts of the plants than on the uppermost parts. In order to investigate the relationship between pea plant growth stage and/ororgan age, and ascochyta blight on whole plants and detached stipules and pods, two experiments were conducted in 2009 and 2010 under controlled conditions. This study showed that plant stage does not influence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…This age-related resistance, commonly called ontogenic resistance (when young tissues are susceptible) or receptivity (when old tissues are susceptible), could be defined as the dynamic modification of tissue receptivity during organ development, triggering resistance/tolerance to pathogenic micro-organisms. Ontogenic resistance has been described for many plant-pathogen systems [e.g., strawberry-powdery mildew (Carisse and Bouchard, 2010), cucurbit fruit— Phytophthora capsici (Ando et al, 2009), tobacco— Phytophthora parasitica (Hugot et al, 1999), apple-apple scab (Li and Xu, 2002), cocoa— Phytophthora megakarya (Takam Soh et al, 2012), pea-powdery mildew (Fondevilla et al, 2006), pea-aschochyta blight (Richard et al, 2012)]. They are therefore common traits but remain underexploited in disease management, principally because of a lack of understanding of the underlying mechanisms and of the potential variability linked to the physiological responses of the host to environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…This age-related resistance, commonly called ontogenic resistance (when young tissues are susceptible) or receptivity (when old tissues are susceptible), could be defined as the dynamic modification of tissue receptivity during organ development, triggering resistance/tolerance to pathogenic micro-organisms. Ontogenic resistance has been described for many plant-pathogen systems [e.g., strawberry-powdery mildew (Carisse and Bouchard, 2010), cucurbit fruit— Phytophthora capsici (Ando et al, 2009), tobacco— Phytophthora parasitica (Hugot et al, 1999), apple-apple scab (Li and Xu, 2002), cocoa— Phytophthora megakarya (Takam Soh et al, 2012), pea-powdery mildew (Fondevilla et al, 2006), pea-aschochyta blight (Richard et al, 2012)]. They are therefore common traits but remain underexploited in disease management, principally because of a lack of understanding of the underlying mechanisms and of the potential variability linked to the physiological responses of the host to environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Equation 5 presents an example of decreasing ontogenic resistance with the unit aging and showing an increase in the rate of infection on the onset of leaf senescence (). Ontogenic resistance was modeled as a pathosystem-specific function [30] as tissues could get less resistant to infection with aging (pisum-aschochyta [31], potato late blight [32]) or, conversely, could become nearly immune in older organs (vitis-powdery mildew [33]). Biotrophic or necrotrophic behaviours were partly reproduced by this function.…”
Section: Resultsmentioning
confidence: 99%
“…a varying disease score upon the canopy height, caused by the development of ascochyta blight on pea fields [20]. This observed behaviour is assumed to be a consequence of two processes: a frequent disease initiation on lower leaves (older and more receptive) and a local dispersion to upper nodes [31]. The bell shape of the disease profiles is interpreted as a gradient of age-based (ontogenic) resistance, as upper and younger leaves are more resistant to infection and lower leaves could become senescent before being fully infected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Means followed within the same cultivar by the same letter do not differ based on a protected LSD test at P ≤ 0.05. progress in the crop (Chongo & Gossen 2001). However, Richard et al (2011) observed that receptivity to M. pinodes, as measured by degree of whole-plant infection, changed very little until senescence was visible.…”
Section: Discussionmentioning
confidence: 99%